2003
DOI: 10.1159/000075361
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Alterations in Free-Circulating Serum DNA in Patients with Ulcerative Colitis

Abstract: Background/Aims: The aim of this study was to find out whether there is free-circulating DNA in the serum of patients with ulcerative colitis and whether it is possible to establish a panel of genetic alterations which might be useful markers for diagnostic purposes, staging, or follow up. Methods: A set of 11 microsatellite markers located on different chromosomes were analyzed in a group of 59 patients with ulcerative colitis. Radiolabeled PCR products from serum and white blood cell DNA were analyzed by aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In terms of their origin, cfDNAs fall into several categories. Endogenous cfDNA sequences are derived from tissues and cells, while exogenous ones are derived primarily from the host microbiome, infectious agents, fetus, and food [ 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of their origin, cfDNAs fall into several categories. Endogenous cfDNA sequences are derived from tissues and cells, while exogenous ones are derived primarily from the host microbiome, infectious agents, fetus, and food [ 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…FcDNA in blood is originated from several sources [5,36,37]. Factors influencing fcDNA clearance include endogenous plasma nucleases, cell surface nucleases, their binding to receptors, and the subsequent intracellular degeneration [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Either amount of these sequences and their quality may be altered within chronic inflammatory disorders, such as systemic lupus erythematodes (SLE) or IBDs [5,6]. Furthermore, a close correlation between the quantity of fcDNA and the course or prognosis of several physiologic and pathologic conditions has been described [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Rauh et al showed for the first time that it is possible to detect cfDNA in the serum of UC patients, and that this cfDNA contained a microsatellite alteration previously identified in mucosa cells from UC patients [69]. A valuable study came from Koike et al, who detected a significantly higher amount of cfDNA in the circulation of mice with DSS-induced colitis compared to the control group.…”
Section: Cell-free Dna In Ibdmentioning
confidence: 99%